Mount Ice Nabalu - Silol, Sarni; Jason, Fazira; Djusni, Elfera; Billi, Dyanallisa; Umpongoh, Robiah; Mattingal, Jennyca; Abdullah, Nor Hanani; Mijon, Jennita Christoper (2016)
Mount Ice Nabalu is about a new ice cream (ChicCream) that we come out with a new flavour and difference tester with the other ice Cream has existing the market today. Our business located at 2nd floor One Borneo, Kota Kinabalu, Sabah. While there are many Ice Cream shop everywhere, Mount ice's Nabalu will attract attention based on our added substance to our customers. Through unheralded customers attention, for Mount ice's nabalu CHICCREAM will slowly but surely our Chiccream will gain market, and will creating long-term relationships with our customers. Moreover, we are believed that we will successfully compete with our competitors in a few years ahead. This is because nowadays people like a new experience for something that them do. They want get a satisfaction from what their invest. We Mount Ice's Nabalu ChicCream, saw the opportunity that this business has the potential of success provided that it is handled efficiently. The is because as we know in order to reduce a stress for example ice Cream sometime can help and because of our weather in Malaysia made people more concern with a sweet tester and cool.